A New View of the Spiral Structure of the Northern Outer Milky Way in Carbon Monoxide - Yan Sun; Ji Yang; Shaobo Zhang; Qing-Zeng Yan; Yang Su; Xuepeng Chen; Xin Zhou; Ye Xu; Hongchi Wang; Min Wang; Zhibo Jiang; Ji-Xian Sun; et al. (The Astrophysical Journal Letters)
Based on 32,162 molecular clouds from the Milky Way Imaging Scroll Painting project, we obtain new face-on molecular gas maps of the northern outer Galaxy. The total molecular gas surface density map reveals three segments of spirals, extending 16–43 kpc in length. The Perseus and Outer arms stand out prominently, appearing as quasi-continuous structures along most of their length. At the Galactic outskirts, about 1306 clouds connect the two segments of the new spiral arm discovered by T. M. Dame & P. Thaddeus ( 2011 ) in the first quadrant and Y. Sun et al. in the second quadrant, possibly extending the arm into the outer third quadrant. Logarithmic spirals can be fitted to the CO arm segments with pitch angles ranging from 4 ^∘ to 12 ^∘ . These CO arms extend beyond previous CO studies and the optical radius, reaching a Galactic radius of about 22 kpc, comparable to the H i radial range.